ECHOES OF THE PAST: A HISTORIOGRAPHICAL AND CULTURAL INQUIRY INTO THE ENDURING LEGACY OF MEDIEVAL ASSAM THROUGH RELIGION, IDENTITY AND SOCIAL INSTITUTIONS - Pathak, Guptajit (ShodhGyan-NU: Journal of Literature and Culture Studies, 2023)
Medieval Assam’s religious, social, and political changes are reflected in its cultural fabric, which has had a significant impact on the region’s current identity. This essay examines how religion, identity, and social structures converged to influence the historical development of medieval Assam in order to provide a historiographical and cultural investigation of the region’s lasting legacy. By combining historical texts, epigraphic evidence, ethnographic accounts, and secondary literature, the study takes a multidisciplinary approach to mapping the ways in which local tribal traditions and religious beliefs particularly Neo-Vaishnavism interacted with socio-political authority and community structures. In order to create a distinctively cultural consciousness, the analysis demonstrates a process of dynamic cultural synthesis that reshaped power dynamics and created community identities.1 The study examines how cultural legacies are passed down, disputed, and rearticulated throughout generations by placing these themes within a historical context. By highlighting plurality, regionalism, and the agency of indigenous communities in forming society structures, the study challenges rigid interpretations history of Assam. Furthermore, this study challenges postcolonial and colonial historiographies that frequently ignore vernacular traditions. In the end, our investigation confirms that Assam’s medieval era had a crucial role in creating the historical memory that still shapes identity today, in addition to laying the groundwork for the development of religious and social conventions.2